Pyrethroid insecticide exposure in school-aged children living in rice and aquacultural farming regions of Thailand - Rohitrattana J; Siriwong W; Robson M; Panuwet P; Barr DB; Fiedler N (Dove Medical Press, 2014)
Juthasiri Rohitrattana,1 Wattasit Siriwong,1,2 Mark Robson,2–4 Parinya Panuwet,5 Dana Boyd Barr,5 Nancy Fiedler3,6 1College of Public Health Sciences, Chulalongkorn University, Bangkok, Thailand; 2Thai Fogarty (ITREOH) International Training and Research in Environmental and Occupational Health Center, Chulalongkorn University, Bangkok, Thailand; 3Environmental and Occupational Health Science Institute, Rutgers University, Piscataway, NJ, USA; 4School of Environmental and Biological Sciences, Rutgers University, New Brunswick, NJ, USA; 5Rollins School of Public Health, Emory University, Atlanta, GA, USA; 6Robert Wood Johnson Medical School, Rutgers University, New Brunswick, NJ, USA Background: Pyrethroid insecticides (PYR) are commonly used in rice farms and household pest control in Thailand. No investigative study has yet been made regarding factors associated with PYR exposure among Thai children. Objective: This study aimed to compare the levels of PYR exposure between children living in rice farms (high-intensity PYR used) and aquacultural areas (low-intensity PYR used) during the wet and dry seasons in Thailand, during which different amounts of PYR are applied. Environmental conditions and common activities of children were used to identify factors associated with PYR exposure. Methods: A cross-sectional study was done during the wet and dry seasons, respectively. A total of 53 participants aged between 6 and 8 years old were recruited from rice farms and aquacultural areas. A parental-structured interview was used to gather information about PYR use, household environments, and participants' activities. First voided morning urine samples were collected for PYR urinary metabolites (ie, 3-phenoxybenzoic acid [3-PBA] and cis/trans-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid [DCCA]) measurements. Hand wipe samples were collected during home visits, to measure PYR residues on the hands. Results and discussion: The concentrations of urinary PYR metabolites were not significantly different between participants who lived in rice farming and those who lived in aquacultural areas, during both wet and dry seasons. Both participant groups had slightly increased urinary PYR metabolites during the wet season compared with the dry season. The results from linear regression analysis revealed that some environmental conditions and activities or practices may be used to predict trends of PYR exposure. Frequency of PYR use in farms (β=0.004) and households (β=0.07), proximity to rice farms (β=0.09), playing in rice farms (β=0.11), and oral exposure from objects exposed to PYR (β=0.08) were likely to be related to increased concentrations of PYR metabolites. These findings suggest that PYR use in rice farms and households may be significant sources of PYR exposure among children living in agricultural areas. However, a bigger sample size may be necessary in a subsequent study, to explore the association between long-term exposure to pesticide and its health effects on children. Keywords: Pyrethroid insecticide, PYR, 3-phenoxybenzoic acid, 3-PBA, cis/trans-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid, DCCA, child health, environment, activity